Systems pharmacology identifies ajugol-mediated NF-κB/caspase-3 inhibition and isoacteoside-driven p62/mTOR-mediated autophagy as key mechanisms of Rehmanniae Radix and its processed form in Alzheimer’s treatment - Han, Xiang; Meng, Xianglong; Wu, Yuhui; Xia, Wei; Xue, Simin; Liu, Xiaoqin; Lyu, Chenzi; Li, Ziang; Yan, Xiaoning; Won Jung, Hyo; Zhang, Shuosheng (Frontiers in Pharmacology, 2025)
BackgroundAlzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by the deposition of senile plaques, neurofibrillary tangles, and neuronal dysfunction, resulting in severe cognitive and memory decline. The root of the Scrophulariaceae plant Rehmannia glutinosa (Gaertn.) DC. (Rehmanniae radix; RR) and its product Rehmanniae radix praeparata (RRP) possess high nutritional and medicinal value. Both show therapeutic potential for AD in traditional medical settings. However, the differences in their bioactive components and the mechanisms of action underlying their anti-AD effects remain unclear.MethodsIn this study, APP/PS1 mice were used as the animal model of AD. Ultra-high-performance liquid chromatography coupled with Q-Exactive tandem mass spectrometry (MS/MS) (UPLC–QE-MS/MS), network pharmacology, proteomics, molecular docking, and 16S rRNA sequencing were used to investigate the differences in the medicinal components of RR and RRP and their mechanisms of action in the treatment of AD. The mechanisms of action of two identified critical components, ajugol and isoacteoside, were further verified in the D-galactose/AlCl3-induced Institute of Cancer Research (ICR) mouse model of AD—with cognitive function evaluated using the Morris water maze and open-field tests—and the amyloid-beta (Aβ)-induced BV2 cell model of inflammation.ResultsAjugol and isoacteoside were identified as the key anti-AD bioactive compounds in RR and RRP, respectively, through UPLC–QE-MS/MS. Integrated network pharmacology, proteomics, and 16S rRNA sequencing implicated neuroinflammation, apoptosis, and autophagy as critical pathways for their anti-AD effects. Subsequently, in vivo and in vitro experiments demonstrated that ajugol exerted its effects mainly by modulating the TLR/NF-κB/NLRP3 and BCL-2/BAX/cytochrome C/caspase-3 pathways, while isoacteoside primarily acted via the LC3-Ⅱ/P62/p-mTOR/mTOR pathway. Ajugol and isoacteoside mitigated cognitive impairment in AD models, decreased Aβ plaque accumulation in hippocampal tissues, and attenuated inflammatory injury-induced cytotoxicity in BV2 microglia, thereby suppressing AD progression.ConclusionIn this work, we systematically elucidated the differential mechanisms underlying the anti-AD effects of ajugol and isoacteoside. We found that ajugol primarily acts via the TLR/NF-κB/NLRP3 and BCL-2/BAX/cytochrome C/caspase-3 pathways, while isoacteoside acts via the LC3-II/P62/p-mTOR/mTOR pathway. These findings establish a foundation for developing RRP-based complementary medicines and functional foods.